Transformative Environmental Conflicts. The case of struggles against large-scale mining in Argentina - Walter, Mariana (2023)
This chapter explores an intriguing case of environmental mobilization, Argentina’s anti-mining movement. This movement has contributed to the cancellation or suspension of about half of the contentious projects they have opposed. Argentina’s national governments have openly supported mining activities as a strategic policy during the past two decades. Nevertheless, actors critical to mining activities have led to the approval of regulations/laws restricting large-scale mining activities in nine out of twenty-three national provinces (including two restrictive laws that were later reverted). This process of mobilization and institutional change is quite unique when compared to other Latin American and worldwide environmental mobilization processes (Scheidel et al. 2020). In this chapter we argue that while the most visible outcomes of mining mobilization are apparently institutional, changes in institutions were possible due to the multi-scalar mobilization of actors that successfully deployed strategies targeted on the different forms of power (institutions, actors/networks and narratives/discourses) that were supporting mining development in the country. This process has led to far-reaching transformations in Argentina’s social and environmental narratives and policies.